Effects of supplemental dietary L-carnitine on growth and body composition of beluga (Huso huso) Juveniles - Mohseni, M.; Seyfabadi, J.; Pourali, H.; Pourkazemi, M.; Bahmani, M. (2008)
The effect of feed supplemented with L-camitine at four levels of 0, 300, 600 and 900mg kg-1 on growth performance and body composition of beluga, H. huso, juveniles was evaluate din two separate trials. In the first trial, 180 juveniles (525±9gw) were fed with the test diet for a period of 71 days, and the trial extended to another 126 days in the second phase by randomly selecting 120 juveniles (870.7±32g) and rearing them with similar diets. All trials, in triplicates, were conducted in circular fiberglass tanks (200cm diameter, 40cm height).The fish were fed 4 times daily to apparent satiation. In the first phase, L-carnitine did not significantly affect mean final weight, feed conversion ratio (FCR) or specific growth rate (SGR) of the fish, however, the fish receiving 900mg kg-1 L-carnation showed better growth increment, SGR and feed efficiency (FE) than those in control group (p³0.05); neither did it significantly affect protein, lipid, moisture or ash as well as leptosomatic index (HSI) (p³0.05). The protein efficiency ratio (PER) was significantly affected by L-carnitine supplemented diet, particularly at 900mg kg-1(p£0.05). In the second phase, fish fed L-carnitine-supplemented diets produced significantly higher W2, SGR and PER than the control group (p£0.05), but HSI decreased significantly (P£0.05).At the end of the trial, the whole body composition of fish did not differ significantly among experimental treatments, but slightly reduced lipid content were observed at 600 and 900mg kg-1 L-carnitine (p£0.05).The results of this study indicated that supplementation of diets with 300-600mg carnitine kg-1 improved growth rate, feed utilization and stimulated protein-sparing effect in this species. Published